The Efficacy of Self Help Cognitive Behavior Therapy in Managing Psychological Distress in Pregnant Women: Self Help Cognitive Behavior Therapy in Managing Psychological Distress - Naz, Saba; Ali, Uzma (Pakistan Journal of Health Sciences, 2025)
Jagtap A, Jagtap B, Jagtap R, Lamture Y, Gomase K. Effects of Prenatal Stress on Behavior, Cognition, and Psychopathology: A Comprehensive Review. Cureus. 2023 Oct; 15(10). doi: 10.7759/cureus.47044. Hasriantirisna H and Nanda KR. Effects of Stress During Pregnancy on Maternal and Fetal Health: A Systematic Review. Advances in Healthcare Research. 2024 Jun; 2(2): 103-15. doi: 10.60079/ahr.v2i2.339. Saur AM, Dos Santos MA. Risk Factors Associated with Stress Symptoms During Pregnancy and Postpartum: Integrative Literature Review. Women and Health. 2021 Aug; 61(7): 651-67. doi: 10.1080/03630242.2021.1954132. Xiong P, Liu M, Liu B, Hall BJ. Trends in the Incidence and Daliys of Anxiety Disorders A: The Global, Regional, and National Levels: Estimates from the Global Burden of Disease Study 2019. Journal of Affective Disorders. 2022 Jan; 297: 83-93. doi: 10.1016/j.jad.2021.10.022. Padhani ZA, Salam RA, Rahim KA, Naz S, Zulfiqar A, Ali Memon Z et al. Prevalence and Risk Factors of Perinatal Depression among Mothers and Fathers in Pakistan: A Systematic Review and Meta-Analysis. Health Psychology and Behavioral Medicine. 2024 Dec; 12(1): 2383468. doi: 10.1080/21642850.2024.2383468. Ishtiaque S, Sultana S, Malik U, Yaqoob U, Hussain S. Prevalence of Antenatal Depression and Associated Risk Factors among Pregnant Women Attending Antenatal Clinics in Karachi, Pakistan. Rawal Medical Journal. 2020 May; 45(2): 434-8. Kanwal F and Yousuf T. Culturally Adapted Trauma-Focused Cognitive Behavior Therapy (CatCBT) for Media Exposure Induced Secondary Traumatic Stress (MEISTS) – A Pilot Study. Remittances Review. 2024; 9(S3): 1145–1168 Khan S, Lovell K, Lunat F, Masood Y, Shah S, Tomenson B et al. Culturally-Adapted Cognitive Behavioural Therapy Based Intervention For Maternal Depression: A Mixed-Methods Feasibility Study. BioMed Central Women's Health. 2019 Jan; 19(1): 21. doi: 10.1186/s12905-019-0712-7. Lovibond SH. Manual for the Depression Anxiety Stress Scales. Sydney Psychology Foundation. doi: 10.1037/t01004-000. Aslam N and Kamal A. Translation, Validation and Effectiveness of Depression, Anxiety and Stress Scale (DASS-21) in Assessing the Psychological Distress among Flood Affected Individuals. Journal of Pakistan Psychiatric Society. 2017; 14(4). Naeem F, Irfan M, Ayub M. Khushi aur Khatoon: zehni dabao aur tanao ka apni madad aap ke tehat elaj: a culturally adapted CBT-based self-help manual for stress. Lahore: Pakistan Association of Cognitive Therapists; 2015. Available from: https://www.researchgate.net/publication/280445205. Amin R, Iqbal A, Naeem F, Irfan M. Effectiveness of a Culturally Adapted Cognitive Behavioural Therapy-Based Guided Self-Help (CACBT-GSH) Intervention to Reduce Social Anxiety and Enhance Self-Esteem in Adolescents: A Randomized Controlled Trial from Pakistan. Behavioural and Cognitive Psychotherapy. 2020 Sep; 48(5): 503-14. doi: 10.1017/S1352465820000284. Khalid A, Haqqani S, Williams C. Guided Self-Help Urdu Version of the Living Life to the Full Intervention for Secondary School Adolescents with Low Mood and Anxiety in Pakistan: A Feasibility Study. Heliyon. 2022 Jul; 8(7). doi: 10.1016/j.heliyon.2022.e09809. Latif M, Husain MI, Gul M, Naz S, Irfan M, Aslam M. Culturally Adapted Trauma-Focused CBT-Based Guided Self-Help (Catcbt GSH) for Female Victims of Domestic Violence in Pakistan: Feasibility Randomized Controlled Trial. Behavioural and Cognitive Psychotherapy. 2021 Jan; 49(1): 50-61. doi: 10.1017/S1352465820000685. Rauf N, Park S, Zaidi A, Malik A, Atif N, Surkan PJ. Self-Reported Problems and Functional Difficulties in Anxious Pregnant Women in Pakistan: The Use of a Patient-Generated Mental Health Outcome Measure. Transcultural Psychiatry. 2024 Aug; 61(4): 689-98. doi: 10.1177/13634615241250206. Latif M, Awan F, Gul M, Husain MO, Husain MI, Sayyed K et al. Preliminary Evaluation of A Culturally Adapted CBT-Based Online Programme for Depression and Anxiety from A Lower Middle-Income Country. The Cognitive Behaviour Therapist. 2021 Jan; 14: e36. doi: 10.1017/S1754470X21000313. Surkan PJ, Malik A, Perin J, Atif N, Rowther A, Zaidi A et al. Anxiety-Focused Cognitive Behavioral Therapy Delivered By Non-Specialists to Prevent Postnatal Depression: A Randomized, Phase 3 Trial. Nature Medicine. 2024 Mar; 30(3): 675-82. doi: 10.1038/s41591-024-02809-x. Schienle A and Jurinec N. Placebo Effects During the Waiting Period for Psychotherapy in Patients with Depression. Current Psychology. 2023 Dec; 42(36): 32024-9. doi: 10.1007/s12144-022-04206-4. Fuhr DC, Sikander S, Vanobberghen F, Weobong B, Rahman A, Weiss HA. Predictors of Spontaneous Remission and Recovery Among Women with Untreated Perinatal Depression in India and Pakistan. Cambridge Prisms: Global Mental Health. 2023 Jan; 10: e34. doi: 10.1017/gmh.2023.26. Dooley RL and McAloon J. The Efficacy of Antenatal Cognitive Behavioural Therapy for Antenatal and Postnatal Depression: A PRISMA-Based Systematic Review and Meta-Analysis. Journal of Affective Disorders. 2025 Feb. doi: 10.1016/j.jad.2025.02.008. Yasar AB, Gündoğmuş İ, Taşdelen R, Taygar AS, Uludağ E, Akça E et al. A Randomized Controlled Trial of the Effect of Cognitive Behavioral Therapy-Based Self-Help Psychotherapy Books on Anxiety and Depressive Symptoms: A Bibliotherapy Study. Düşünen Adam-Psikiyatri ve Nörolojik Bilimler Dergisi. 2024; 37(1): 5-14. doi: 10.14744/DAJPNS.2024.00232. Li X, Laplante DP, Paquin V, Lafortune S, Elgbeili G, King S. Effectiveness of Cognitive Behavioral Therapy for Perinatal Maternal Depression, Anxiety and Stress: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. Clinical Psychology Review. 2022 Mar; 92: 102129. doi: 10.1016/j.cpr.2022.102129. Wan Mohd Yunus WM, Matinolli HM, Waris O, Upadhyaya S, Vuori M, Korpilahti-Leino T et al. Digitalized Cognitive Behavioral Interventions for Depressive Symptoms During Pregnancy: Systematic Review. Journal of Medical Internet Research. 2022 Feb; 24(2): e33337. doi: 10.2196/33337. Gellatly J, Bower P, Hennessy SU, Richards D, Gilbody S, Lovell K. What Makes Self-Help Interventions Effective in the Management of Depressive Symptoms? Meta-Analysis and Meta-Regression. Psychological Medicine. 2007 Sep; 37(9): 1217-28. doi: 10.1017/S0033291707000062.